Interventions to Support Behavioral Self-Management of Chronic Diseases - Allegrante, John P; Wells, Martin T; Peterson, Janey C (Annual review of public health, 2019)
A majority of the US adult population has one or more chronic conditions that require medical intervention and long-term self-management. Such conditions are among the 10 leading causes of mortality; an estimated 86% of the nation's $2.7 trillion in annual health care expenditures goes toward their treatment and management. Patient self-management of chronic diseases is increasingly essential to improve health behaviors, health outcomes, and quality of life and, in some cases, has demonstrated effectiveness for reducing health care utilization and the societal cost burden of chronic conditions. This review synthesizes the current state of the science of chronic disease self-management interventions and the evidence for their effectiveness, especially when applied with a systematic application of theories or models that account for a wide range of influences on behavior. Our analysis of selected outcomes from randomized controlled trials of chronic disease self-management interventions contained in 10 Cochrane systematic reviews provides additional evidence to demonstrate that self-management can improve quality of life and reduce utilization across several conditions.